2020
DOI: 10.5194/acp-20-3191-2020
|View full text |Cite
|
Sign up to set email alerts
|

The long-term trend and production sensitivity change in the US ozone pollution from observations and model simulations

Abstract: Abstract. We investigated the ozone pollution trend and its sensitivity to key precursors from 1990 to 2015 in the United States using long-term EPA Air Quality System (AQS) observations and mesoscale simulations. The modeling system, a coupled regional climate–air quality model (CWRF-CMAQ; Climate-Weather Research Forecast and the Community Multiscale Air Quality), captured well the summer surface ozone pollution during the past decades, having a mean slope of linear regression with AQS observations of ∼0.75.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 74 publications
4
19
0
Order By: Relevance
“…Even during the wintertime, under low levels of solar radiation, concentrations of OH can reach 3 × 10 6 molecule cm −3 in Beijing (Slater et al, 2020), which is similar to the OH concentrations observed in other urban centres in European cities during the summer months (Whalley et al, 2018). Similar to findings from radical observations and subsequent modelling activities in forested regions (Whalley et al, 2011), which are characterised by high VOC emissions and relatively low NO x concentrations, the observations and modelling studies in China in summer (Hofzumahaus et al, 2009;Lu et al, 2012;Lu et al, 2013) revealed that the high OH concentrations could only be explained if an additional source of OH, from recycling peroxy radicals to OH, was added to the model. An updated isoprene scheme (Peeters et al, 2009(Peeters et al, , 2014, which included isomerisation reactions of the isoprene-derived RO 2 radicals, was unable to reconcile the OH observations, however.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Even during the wintertime, under low levels of solar radiation, concentrations of OH can reach 3 × 10 6 molecule cm −3 in Beijing (Slater et al, 2020), which is similar to the OH concentrations observed in other urban centres in European cities during the summer months (Whalley et al, 2018). Similar to findings from radical observations and subsequent modelling activities in forested regions (Whalley et al, 2011), which are characterised by high VOC emissions and relatively low NO x concentrations, the observations and modelling studies in China in summer (Hofzumahaus et al, 2009;Lu et al, 2012;Lu et al, 2013) revealed that the high OH concentrations could only be explained if an additional source of OH, from recycling peroxy radicals to OH, was added to the model. An updated isoprene scheme (Peeters et al, 2009(Peeters et al, , 2014, which included isomerisation reactions of the isoprene-derived RO 2 radicals, was unable to reconcile the OH observations, however.…”
Section: Introductionsupporting
confidence: 80%
“…There has been an increasing growth in photochemical oxidant studies conducted in China, where radical observations have been performed over the past decade, with the PKU and Juelich groups leading these efforts. The first radical observations took place in the summer of 2006, with observations made in the Pearl River Delta (PRD) region (Hofzumahaus et al, 2009;Lu et al, 2012;PRIDE-PRD-2006) and also in suburban Beijing (Lu et al, 2013;CARE-Beijing 2006). These campaigns revealed a strong atmospheric oxidation capacity, with elevated levels of OH and HO 2 in these regions, with OH concentrations up to 2.6 × 10 7 molecule cm −3 and HO 2 concentrations up to 2.5 × 10 9 molecule cm −3 reported (Lu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar reductions in these primary pollutants are echoed in other countries across the globe. In the US this reduction in primary emissions is reflected in a ~0.4 ppbv yr -1 reduction in peak O3 (He et al, 2020). In China, however, despite reductions in primary emissions, the concentration of ground-level ozone has been gradually increasing between 2013 -2017 (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The downward trends in NOx 55 emissions have been verified by ground and satellite observations in large cities (Tong et al, 2015) and in the eastern United States (Zhou et al, 2013;Krotkov et al, 2016). Because of the substantial emission reductions, ground-level ozone concentrations decreased ubiquitously across the US (Hogrefe et al, 2011;Simon et al, 2015;He et al, 2020).…”
Section: Introduction 50mentioning
confidence: 99%
“…All of the high-resolution simulations, including the Control run, perform better than the NAQFC run (Fig. 9), highlighting the benefit of using a high-resolution modeling system for predicting short-lived chemical species (He et al, 2020;Qu et al, 2019), this episode, which occurred during a well-designed field campaign, offers a rare opportunity to assess how well a state-of-the-science air quality model can predict a high O3 pollution event…”
mentioning
confidence: 99%